EEG correlates of egocentric and altercentric biases in forensic cases with borderline personality - Rochas, Vincent; Montandon, Marie-Louise; Rodriguez, Cristelle; Herrmann, François R.; Eytan, Ariel; Pegna, Alan J.; Michel, Christoph M.; Giannakopoulos, Panteleimon (Frontiers in Neuroscience, 2025)
People tend to consider others’ perspective when judging their own (altercentric interference, AI) or other (egocentric interference, EI) divergent views. Borderline (BDL) and antisocial personalities are associated with significant changes in EI and AI. Combining the dot perspective-taking task with high-density EEG recordings, our study explores the correlations between EI and AI in cases with BDL diagnosis and court-ordered measures (BDL-COM; n = 14) compared to age-matched healthy controls (n = 24). In Inconsistent trials, controls displayed significant activation of brain generators, which was absent in BDL-COM patients. For the Self-Inconsistent stimuli (altercentric bias), controls showed increased activity in the left superior frontal gyrus between 58 and 74 ms and the left inferior frontal gyrus between 279 and 303 ms. Similar differences were observed for Other-Inconsistent stimuli (egocentric bias) in the precentral gyri and inferior frontal gyrus between 274 and 296 ms. These findings suggest that AI involves an early activation of brain generators in central executive and mentalizing areas. EI is associated with an increased activation of the mirror neuron system based on self–other distinction. These EEG data indicate that BDL-COM patients display significant difficulties activating all of the brain generators involved in the processing of conflicting viewpoints in visual perspective-taking.